Post-Endovascular Abdominal Aortic Aneurysm Repair Abdominal Pain: A Learning Experience. (July 2019) - Kichloo, Asim; Khan, M. Zatmar; Zain, El-Amir; Vipparla, Navya Sree; Wani, Farah
Abdominal aortic aneurysm (AAA) is one of the important pathologies involving the abdominal aorta, as it can have adverse consequences if it goes unnoticed or untreated. AAA is defined as an abnormal dilation of the abdominal aorta 3 cm or greater. Endovascular abdominal aortic aneurysm repair (EVAR) has recently emerged as a treatment modality for AAA. It does have a few inherent complications that include endoleak, endograft migration, bleeding, ischemia, and compartment syndrome. This case report discusses a patient who came in with abdominal pain and a pulsatile mass, which raised concerns regarding endoleak. The patient had a 9.9-cm AAA, which was repaired in the past, as was made evident by computed tomography findings of the stent graft in the aneurysmal segment. This case stands out because it highlights the importance of comparing the size of the AAA at the time of the EVAR to the current scenario where the patient presents with abdominal pain of unknown etiology. Also, this case report highlights the importance of computed tomography and other imaging forms in following-up with patients who have EVAR for AAAs.